KEMAMPUAN BERPIKIR KRITIS MATEMATIS SISWA KELAS XI SMK PADA MATERI MATRIKS DENGAN PENERAPAN PENDEKATAN RECIPROCAL TEACHING - Meri Siti Maryam; Luvy Sylviana Zanthy (Departement of Mathematics Education, 2019)
This study aims to analyze the effect of applying the reciprocal teaching approach in an effort to improve students' critical thinking skills in the XI-IOP B class of SMK 1 Cimahi in the matrix material. This research is a type of classroom action research consisting of 2 (two) cycles based on the mathematics teacher's syllabus in class XI-IOP B. Each cycle is based on the objectives to be achieved in learning. The cycle in this study includes the following procedures: (1) Planning; (2) Acting; (3) Observation and evaluation; (4) Reflection. Based on the results of research conducted on class XI-IOP B students of SMK 1 Cimahi that the use of the reciprocal teaching approach can improve mathematical critical thinking skills, namely: (1) the response and learning outcomes shown by students in the second cycle are very good and (2) Tests of mathematical representation ability of students in each cycle experienced a good improvement, until the last cycle showed 87%. Based on the results of the test it can be seen that there are only 4 students out of a total of 29 students who have grades below 65. Learning by applying the reciprocal teaching approach is very effective to be used in the learning process.